PSYCHOLOGICAL FOUNDATIONS OF SOCIAL ADAPTATION OF STUDENTS WITH DISABILITIES (American Journal of Interdisciplinary Research and Development, 2023)
This article is one of the current problems in which the psychological foundations of social adaptation of students with disabilities, the need to conduct developmental education with anomalous children, methods of correction, compensation and ways to implement them are studied.